Catheter ablation for fascicular ventricular tachycardia: A systematic review. (1st February 2019) - Creta, Antonio; Chow, Anthony W.; Sporton, Simon; Finlay, Malcolm; Papageorgiou, Nikolaos; Honarbakhsh, Shohreh; Dhillon, Gurpreet; Graham, Adam; Patel, Kiran H.K.; Dhinoja, Mehul; Earley, Mark J.; Hunter, Ross J.; et al.
Abstract: Introduction: Catheter ablation has been evaluated as treatment for fascicular ventricular tachycardia (FVT) in several single-centre cohort studies, with variable results regarding efficacy and outcomes. Methods: A systematic search was performed on PubMed, EMBASE and Cochrane database (from inception to November 2017) that included studies on FVT catheter ablation. Results: Thirty-eight observational non-controlled case series comprising 953 patients with FVT undergoing catheter ablation were identified. Three studies were prospective and only 5 were multi-centre. Eight-hundred and eighty-four patients (94.2%) had left posterior FVT, 25 (3.4%) left anterior FVT and 30 (2.4%) other forms. In 331 patients (41%), ablation was performed in sinus rhythm (SR). The mean follow-up period was 41.4 ± 10.7 months. Relapse of FVT occurred in 100 patients (10.7%). Among the 79 patients (8.3%) requiring a further procedure after the index ablation, 19 (2%) had further FVT relapses. Studies in which ablation was performed in FVT had similar success rate after multiple procedures compared to ablation in SR only (95.1%, CI95% 92.2–97%, I 2  = 0% versus 94.8%, CI95% 87.6–97.9%, I 2  = 0%, respectively). Success rate was numerically lower in paediatric-only series compared to non-paediatric cases (90.0%, CI95% 82.1–94.6%, I 2  = 0% versus 94.3%, CI95% 92.2–95.9%, I 2  = 0%, respectively). Conclusion: Data derived from observational non-controlled case series, with low-methodological quality, suggest that catheter ablation is a safe and effective treatment for FVT, with a 93.5% success rate after multiple procedures. Ablation during FVT represents the first-line and most commonly used approach; however, a strategy of mapping and ablation during SR displayed comparable procedural results to actively mapping patients in FVT and should therefore be considered in selected cases where FVT is not inducible. Highlights: We performed a systematic analysis including studies on fascicular tachycardia ablation. Catheter ablation is a safe and effective treatment for fascicular tachycardia. Success rate is 93.5% after multiple procedures. Ablation during sinus rhythm had similar results compared to ablation during tachycardia.